Kritična analiza raziskav SJM o športno-rekreativni dejavnosti v Sloveniji - Poteko, Kaja (Šport (Ljubljana), 2022)
This text takes the longitudinal Slovenian Public Opinion (SPO) survey on sports and leisure activities in Slovenia as its starting point and aims, in the context of reviewing previous SPO research in this area, to (a) highlight some SPO results and critically evaluate their analyses, (b) add results and analysis of the SPO 2021 from the perspective of socio-demographic factors, and (c) look for ways to complement existing approaches in this research area. Among the findings of this study is the weakness of previous interpretations and analyses of the SPO, which - instead of problematizing and critically addressing them - often reproduce existing social norms and modern imperatives. Based on the results of related foreign research efforts in this area, the need is recognized to complement quantitative approaches with qualitative ones that would allow going beyond the level of surface description and deepening it by identifying and explaining its causes. This would contribute significantly to finding more informed and nuanced solutions to the problems identified.
Keywords: raziskave; Slovenija; Slovensko javno mnenje; šport